Incidental finding of Bochdalek hernia in an adult: a case report - Balzano, Rosario Francesco; Fascia, Giacomo; Sciacqua, Alessio; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
A Bochdalek hernia, also known as a congenital diaphragmatic hernia (CDH), is a type of hernia that occurs in infants. The diaphragm, the muscle that separates the chest cavity from the abdominal cavity, is characterized by a hole or gap during birth. This opening allows the abdominal organs, such as the stomach, intestines, or liver, to pass through the thoracic cavity. Here, we report a 56-year-old male patient who came to our hospital because of rectal bleeding, symptoms unrelated to the hernia. We performed a Computed Tomography (CT) scan with contrast enhancement to find the cause of the bleeding and as an incidental finding we diagnosed the hernia: it is very rare to find a silent Bochdalek hernia for more than 50 years.